Sistem Informasi Pembelian dan Penjualan Pada Ternama Konveksi Berbasis WEB - Rahmatia; Avid Inang Rum (LPPM UNIVERSITAS INSAN PEMBANGUNAN INDONESIA, 2025)
Ternama Konveksi still uses spreadsheets to record sales and purchase transactions, which leads to data entry errors, duplication, and delays in reporting. This study aims to address these issues by designing a web-based Sales and Purchase Information System using the waterfall method. The system improves transaction data entry speed, minimizes human errors, and stores data in a structured database. User Acceptance Testing (UAT) results show a user satisfaction rate of 90,89%, categorized as “Excellent.”